THE ABILITY OF THE SECOND YEAR STUDENTS OF SMPN 32 PEKANBARU IN USING APPROPRIATE PREPOSITION IN A READING TEXT - Lydia Kusdyanti Iasya; Fadly Azhar; Afrianto Afrianto (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract: The purpose of this study is to find out the ability of the second year students of SMPN 32 Pekanbaru in using appropriate preposition in a reading text. In particular, this research focuses on their ability in using preposition of place, time and direction. There were 40 students selected using cluster random sampling as sample of this quantitative study. The data were collected using a reading text test with 20 multiple choice tests. The try out was conducted to check the validity and reliability of the test. It was found that the ability of the second year students in using appropriate preposition is poor to average level with mean score 58,88. This research recommended the students to make themselves familiar with more elaborated use of prepositions. Students can also comprehend more about the conceptualization of prepositions in many contexts by practicing writing and speaking that would require them to use prepositions. Further research can focus on how to overcome the high level of difficulties of English prepositions materials.Keywords: Students’ Ability, Preposition.